2011
DOI: 10.1007/978-3-642-24500-8_5
|View full text |Cite
|
Sign up to set email alerts
|

GrabApple: The Design of a Casual Exergame

Abstract: Abstract. Many people do not get the recommended 30 minutes of exercise per day, which can result in health problems such as obesity, muscle atrophy and chronic disease. Based on the principles of casual games and exergames, we propose and define casual exergames for motivating people to exercise in multiple small chunks of time throughout the day. We designed, implemented, and tested a casual exergame called GrabApple. Our preliminary results show that users enjoyed playing the casual exergame and that in jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…These perks have been associated with vigorous physical activity (Mueller et al, 2003) and the "casual" aspect of these games that, according to Gao and Mandryk (2011, p. 36), motivate players "to exercise at a moderate intensity for short periods of play" and provide benefits associated with frequent bursts of moderate-intensity activity (Gao & Mandryk, 2011. However, many of these positive outcomes do not come exclusively as a result of arduous physical activity.…”
Section: Background Of Each Design Casementioning
confidence: 99%
“…These perks have been associated with vigorous physical activity (Mueller et al, 2003) and the "casual" aspect of these games that, according to Gao and Mandryk (2011, p. 36), motivate players "to exercise at a moderate intensity for short periods of play" and provide benefits associated with frequent bursts of moderate-intensity activity (Gao & Mandryk, 2011. However, many of these positive outcomes do not come exclusively as a result of arduous physical activity.…”
Section: Background Of Each Design Casementioning
confidence: 99%
“…To help people add these small chunks of physical activity throughout the day, casual exergames [10] apply the principles of casual game design to the design of exergames: most importantly, they allow players to engage in physical activity in short bouts. Specifically, casual exergames are defined as computer games that players can learn easily and access quickly, using simple rules and game mechanics, to motivate them to exercise at a moderate intensity for short periods of play [10].…”
Section: Casual Exergamesmentioning
confidence: 99%
“…To help people add these small chunks of physical activity throughout the day, casual exergames [10] apply the principles of casual game design to the design of exergames: most importantly, they allow players to engage in physical activity in short bouts. Specifically, casual exergames are defined as computer games that players can learn easily and access quickly, using simple rules and game mechanics, to motivate them to exercise at a moderate intensity for short periods of play [10]. Research on casual exergames has shown that as little as ten minutes of casual exergame play can produce moderate-intensity exertion levels, improving players' affective states and providing significant levels of acute cognitive benefits compared to sedentary casual games [9] (i.e., can improve post-play ability of players to focus attention).…”
Section: Casual Exergamesmentioning
confidence: 99%
See 2 more Smart Citations